(untitled) (LEARNing Landscapes, 2012)
In this article, we explore how the library teacher of an Italian preschool with a special mission focused on books, stories, and the imagination uses group literacy activities as a context for encouraging shared meaning making through creative experiences. We take readers inside one day at the Italian Preschool, Filastrocca, providing detailed descriptions and analysis of interactions and activities. We suggest that elaborate extended dialogue among children and the teacher, promotion of empathy through opportunities to take others’ perspectives (including book characters’), and group engagement in shared and multi-faceted creativity are important characteristics related to meaning making in the context of relationships. Encouraging creative exploration and play across all domains of intelligence allows the children to develop their individual strengths into a product uniquely theirs.